Influences of interaction between cement and ionic paraffin emulsion on cement hydration - Huo, Jinyang; Wang, Zhenjun; Zhang, Tonghuan; He, Rui; Chen, Huaxin (Construction & building materials, 2021)
Polymers have been used in cement materials for a long time. Notably, the polymer usage has a significant impact on cement hydration. In this work, the influences of interaction between cement and ionic paraffin emulsions (i. e., anionic paraffin emulsion (A), cationic paraffin emulsion (C), and nonionic paraffin emulsion (N), respectively) on cement hydration were experimentally investigated by calorimetry, UV–Vis spectroscopy measurement, depletion measurement, and XRD measurement, in which the hydration rate, hydration degree, and evolution of hydration products were assessed. Results reveal that anionic and cationic paraffin emulsions exhibit stronger hindrance effects to hydration kinetics than nonionic paraffin emulsion by comparison of b value based on the factorial design system. In addition, the stronger the adsorption between ionic paraffin emulsions and cement (decrease in absorbance; increase in adsorption ratio), the lower the hydration rate, hydration degree and the main diffraction peak intensity of hydration products. Meanwhile, the comparison of absorbance, adsorption ratio, and the main diffraction peak intensity of hydration products shows that anionic and cationic paraffin emulsions have strong adsorption on the surface of cement grains and/or cement hydration products, and have a strong hindrance on the dissolution of tricalcium silicate and the formation of portlandite and ettringite.